Blackjacking : security threats to Blackberry devices, PDAs, and cell phones in the enterprise - Hoffman, Daniel (Daniel V.), 1972- (Wiley Pub., 2007)
Is someone waiting to pick off your BlackBerry?. Today, it is almost impossible to do business without a cell phone and a BlackBerry or PDA. These devices are a lifeline for companies large and small. And nobody knows this better than a hacker.